2020
DOI: 10.3390/ijerph17030956
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Troponin T Release after Football 7 in Healthy Children and Adults

Abstract: The objective of this study was to compare the release of cardiac troponin T (cTnT) after a football 7 match between two cohorts of children and adult players. Thirty-six male football players (children = 24, adult = 12) played a football 7 match, and cTnT was measured before, and 3 h after exercise. Concentrations of cTnT were compared between groups and time, and correlated with participants’ characteristics, as well as internal and external exercise load. Cardiac troponin T was elevated in all participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(46 citation statements)
references
References 28 publications
2
44
0
Order By: Relevance
“…Data on children and adolescents 8,9,16,25,31,[36][37]52,64 confirm the findings observed in adults. A systematic review 1 and meta-analysis including 336 adolescents (mean age 15.1 6 2.3 years) demonstrated that cTnT and cTnI had a similar kinetic of postexercise peaks (at 2-5 hours for cTnT and 3-6 hours for cTnI).…”
Section: Studies In Different Types Of Sport Sex Age and Ethnicitysupporting
confidence: 82%
See 2 more Smart Citations
“…Data on children and adolescents 8,9,16,25,31,[36][37]52,64 confirm the findings observed in adults. A systematic review 1 and meta-analysis including 336 adolescents (mean age 15.1 6 2.3 years) demonstrated that cTnT and cTnI had a similar kinetic of postexercise peaks (at 2-5 hours for cTnT and 3-6 hours for cTnI).…”
Section: Studies In Different Types Of Sport Sex Age and Ethnicitysupporting
confidence: 82%
“…8 In a meta-analysis including 14 studies and 336 adolescents, 1 age had a negative correlation with cTnT postexercise increase ( P < 0.01) and no correlation with cTnI ( P = 0.33). In a study 9 on 12 adults (37.5 ± 12.7 years) and 24 adolescents (10.7 ± 1.6 years) after football-7, age ( P < 0.01), body mass ( P = 0.001), and height ( P < 0.001) were associated with baseline cTnT values, but not with postexercise peaks values. The effects of sex have been poorly investigated, 8,23,26,32,45,63 and female athletes are usually underrepresented in studies on athletes.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…5,24 It has been reported that these values might vary depending on age and sex, 25 and previously suggested the need to report on age-and sex-specific population cTn values in children and adolescents. 26 In this regard, previous studies found similar baseline concentrations of cTn between adolescent and adult athletes, 7,8,27 and among adolescent athletes at different maturational stages. 7,9,12 However, in the present study we found that swimmers at Tanner-V had higher resting cTnT than those in I -III, and swimmers in Tanner-IV higher than those in II (Table 1), suggesting that normal values might be higher during late-puberty.…”
Section: Discussionmentioning
confidence: 66%
“…These differences, together with the ones found in the group of non-detected, coincide with previous findings, suggesting that the highest cTnT elevations (both, ∆ Post 0h and ∆ Post 3h) occur in better trained athletes (experience, HR max), 18,28 that achieve higher exercise internal loads (% HR peak and % HR mean) during the test. 4,27 This suggests that not only maturation but also other factors affect the magnitude of increase in cTnT after intense exercise. In spite of that, training status and exercise load could only partially explain the high variability in the exercise-induced elevation of cTnT.…”
Section: Discussionmentioning
confidence: 99%